Analisis Strategi Pemasaran Syariah Berbasis Maqashid Syariah Pada Penjualan Produk Pakaian Muslimah di Branded Moslemwear - Aini, Atica Qurrotun; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2025)
This study aims to analyze the marketing strategy sharia based on maqashid sharia in the sale of Muslim clothing products at Branded Moslemwear. The study used a qualitative approach with a case study method, where data was collected through interviews, observations, and documentation, then analyzed using NVivo software. The results showed that Branded Moslemwear implemented a marketing strategy based on the 4P marketing mix (Product, Price, Place, Promotion) which was adjusted to the principles of maqashid sharia, namely maintaining religion (hifzh al-din), soul (hifzh al-nafs), wealth (hifzh al-mal), reason (hifzh al-aql), and descendants (hifzh al-nasl). The product strategy is focused on halal, comfortable, and sharia-compliant Muslim clothing. Prices are set fairly by paying attention to quality and providing discounts. Distribution is carried out through physical stores, online platforms, and resellers to expand market reach. Promotion is carried out transparently through social media and marketplaces, with education about the importance of dressing in accordance with sharia. The implementation of maqashid sharia in marketing not only increases business profits but also creates blessings and welfare for customers.